Assessment of Anthropogenic Activities, Environmental Literacy and Management Practices Impacting Lake Bosomtwe - OWUSU-BATENG, Godfred; AGYEMANG, Thomas Kwaku; AMPOFO-YEBOAH, Akwasi; SARPONG, Kofi (International Journal of Environmental, Sustainability, and Social Science, 2024)
The communities in the Bosomtwe basin depend on Lake Bosomtwe for their livelihoods. However, the lake has continued to experience human-driven degradation in recent times. We conducted a survey of the main anthropogenic perturbations of the lake, the level of awareness of the communities of anthropogenic interventions and their effects on lake health, and the effectiveness of its management practices using a structured questionnaire administered to 350 respondents. Data were analyzed using non-parametric Kruskal Wallis and Mann Whitney U-tests. Crop farming, fishing, fish mongering, animal rearing, timber harvesting, hospitality operations, washing, other trades, and illegal mining were the anthropogenic interventions of the most devastating consequence, promoted by a low level of education and environmental awareness. Although the regards for directives of the traditional authority to govern the lake declined subtly, the situation is worsening due to inadequate resources for the Bosomtwe District Assembly, the government agency responsible for coordinating the activities of stakeholders of the lake and providing an effective decision-making basis for its conservation. The results, which have direct practical implications for water management, suggest the need for well-coordinated policies and strategies for law enforcement and education of basin communities on the causes and effects of lake degradation.